2019
DOI: 10.1182/blood-2019-125968
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of CD117 Antibody Drug Conjugate Enables Autologous Gene-Modified Hematopoietic Stem Cell Transplant (Gene Therapy) in Nonhuman Primates

Abstract: Autologous hematopoietic stem cell transplantation (Auto-HSCT) with gene-modification techniques represents a potential cure for multiple genetic blood diseases. Despite its broad curative potential, auto-gene modified HSCT is currently limited due to morbidity/mortality from cytotoxic chemotherapy-based conditioning, including risks of secondary malignancies, organ toxicity, and infertility. To overcome these limitations, we have developed antibody drug conjugates (ADC) targeting CD117 (C-KIT) to specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…By simultaneously targeting the stem cell compartment and malignant cells, the therapeutic goals of HSCT can hypothetically be achieved with toxicities largely confined to the hematopoietic system. Indeed, recent work in murine models (14,15,19,20,22), non-human primates (52,53), and early human trials (54) have demonstrated the feasibility and high efficacy of antibody and ADC-based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…By simultaneously targeting the stem cell compartment and malignant cells, the therapeutic goals of HSCT can hypothetically be achieved with toxicities largely confined to the hematopoietic system. Indeed, recent work in murine models (14,15,19,20,22), non-human primates (52,53), and early human trials (54) have demonstrated the feasibility and high efficacy of antibody and ADC-based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, promising results have been recently reported with use of antibody-drug conjugate (ADCs) for HSCT in both humanized mouse models and nonhuman primates, as well as for autologous gene therapy, and they are expected to translate soon into clinical trials. 17,28,29 These observations will be instrumental to extend a nongenotoxic regimen to patients undergoing secondary HSC transplant for loss of chimerism or insufficient thymic output.…”
Section: Discussionmentioning
confidence: 99%
“… 41 To our knowledge, only one report has described the use of a single-agent CD117-targeting immunotoxin to facilitate engraftment of LV-modified HSPCs. 42 Autologous CD34 + HSPCs from rhesus macaques were modified with a β-globin construct and successfully engrafted under CD117-amanitin conditioning. In contrast to our study, these studies did not involve production of a secreted, foreign therapeutic gene product that is known to be highly immunogenic (i.e., fVIII in HA), a unique challenge that requires the induction of sufficient immune tolerance to support lifelong expression of a new circulating protein.…”
Section: Discussionmentioning
confidence: 99%